THE DEVELOPMENT OF INFORMATION RESOURSE FOR INNOVATION ACTIVITY OF A COMPANY - Karina Vladikovna Martirosyan; Alexandr Vitalyevich Martirosyan; Alexandr Sergeevich Zyuzin (Современная наука и инновации)
The article deals with methods of development of information recourses. Particular attention is paid to structuring of content on innovation company activity. It has been demonstrated how implemented information resource.